Ultrasound-Guided Interscalene Block: Reevaluation of the "Stoplight" Sign and Clinical Implications. Issue 4 (July 2016) - Franco, Carlo D.; Williams, James M.
Abstract : Background and Objectives: The "stoplight" sign is a frequently described image during ultrasound-guided interscalene block, referring to 3 hypoechoic structures found between the anterior and middle scalene muscles. This study was designed to establish the ultrasound-anatomy correlation of this sign and to find any other anatomical features within the roots that could help with the interpretation of the ultrasound images obtained at the interscalene level. Methods: We performed 20 dissections of the brachial plexus in 10 embalmed human cadavers and systematically analyzed and measured the roots of C5 to C7 and then correlated these findings with ultrasonographic images on file. Results: We found that the C5 root is significantly smaller than either C6 or C7 ( P < 0.0001). We also found that C6 and C7, but not C5, frequently present macroscopic evidence of intraroot splitting visible to the naked eye. We also found that the roots of C5 and C6, but not of C7, present frequent variations in their relationship with the scalene muscles. Conclusions: Our results provide the anatomic basis to define the stoplight sign as one made of, from cephalad to caudal, the root of C5, the upper fascicle(s) of C6, and the lower fascicle(s) of C6 without contribution from C7. The important clinical implication is that an injection attempted between what is commonly perceived as the gap between C6 and C7 would indeed be an intraneural injection at C6, which could potentially spread toward the neuraxial space.